The effectiveness of using STS approach in teaching science on developing intermediate stage students' achievement and on realizing some technology education objectives - Al Zahrani, Hamdan Mohammed Hamdan (Journal of Educational and Psychological Sciences, 2018)
The research aimed at Identify the effectiveness of using science, technology and society approach in teaching science subject on developing academic achievement and achieving some of the objectives of technological education for the intermediate stage students, and to achieve these objectives the research depended on using the experimental method based on the design of the two groups (experimental & control), and designed a number of tools, represented in the following: rebuild an unite from the curriculum in the light of science, technology and society approach and preparing teacher's guide, and were also built the achievement test and technological skills test. After Making sure of the validity of the research tools and measured its stability, it's were applied to the research sample, which was (59) students from the first grade of intermediate stage, and were divided to (30) student in the experimental group and (29) student in the control group.Results: The research resulted in the following outcomes: there is an effectiveness of using science, technology and society approach in teaching science subject on developing academic achievement and achieving some of the objectives of technological education, there were statistically significant differences in the post- test for achievement and technological skills between the experimental and control groups in favor of the experimental group.In the light of the outcomes of this research, it recommended a set of recommendations was highlighted: It is necessity to include the objectives of technological education in the curriculum of intermediate stage; especially in science curriculum, and also it is necessity to train teachers to use this approach in a way to gain them skills of teaching the technological education, and make an analytical study to determine the range of the technological education objectives which are included in science subjects , in various stages of education.
Keywords: entrance to science; technology and society; technological education goals; science teaching; academic achievement; middle school students